Attention-deficit/Hyperactivity disorder: a current overview - Banaschewski, Tobias (Deutsches Ärzteblatt, 2017)
Attention-deficit/hyperactivity disorder (ADHD; according to the DSM-5) (1) and hyperkinetic disorder (HKD; according to the ICD-10) (2) describe a childhood-onset developmental disturbance that persists for at least six months and across different...